Radial Velocity and Astrometric Evidence for a Close Companion to Betelgeuse - Morgan MacLeod; Sarah Blunt; Robert J. De Rosa; Andrea K. Dupree; Thomas Granzer; Graham M. Harper; Caroline D. Huang; Emily M. Leiner; Abraham Loeb; Eric L. Nielsen; Klaus G. Strassmeier; Jason J. Wang; et al. (The Astrophysical Journal)
We examine a century of radial velocity, visual magnitude, and astrometric observations of the nearest red supergiant, Betelgeuse, in order to reexamine the century-old assertion that Betelgeuse might be a spectroscopic binary. These data reveal Betelgeuse varying stochastically over years and decades due to its boiling, convective envelope, periodically with a 5.78 yr long secondary period (LSP), and quasiperiodically from pulsations with periods of several hundred days. We show that the LSP is consistent between astrometric and radial velocity data sets, and argue that it indicates a low-mass companion to Betelgeuse, less than a solar mass, orbiting in a 2110 day period at a separation of just over twice Betelgeuse’s radius. The companion star would be nearly 20 times less massive and a million times fainter than Betelgeuse, with similar effective temperature, effectively hiding it in plain sight near one of the best-studied stars in the night sky. The astrometric data favor an edge-on binary with orbital plane aligned with Betelgeuse’s measured spin axis. Tidal spin–orbit interaction drains angular momentum from the orbit and spins up Betelgeuse, explaining the spin–orbit alignment and Betelgeuse’s anomalously rapid spin. In the future, the orbit will decay until the companion is swallowed by Betelgeuse in the next 10,000 yr.